2012
DOI: 10.1002/jbm.b.32748
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic contamination of coarse‐grained and nanostructured nitinol surfaces induced by chemical treatment in hydrofluoric acid

Abstract: XPS measurements of coarse-grained and nanostructured nitinol (Ni 50.2 Ti 49.8 ) before and after chemical treatment in hydrofluoric acid (40% HF, 1 min) are presented. The nanostructured state, providing the excellent mechanical properties of nitinol, is achieved by severe plastic deformation. The near-surface layers of nitinol were studied by XPS depth profiling. According to the obtained results, a chemical treatment in hydrofluoric acid reduces the thickness of the protective TiO 2 oxide layer and induces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Arsenic is naturally present in CaF 2 in the trivalent As-III state and is impossible to completely remove [39], which can explain why traces of As are present even in the purest commercially available hydrofluoric acid [40]. We observed a similar result for the surface of coarse-grained and nanostructured nitinol after etching the nitinol in hydrofluoric acid (HF 40%, for 1 min) [41]. The XRD patterns of the anodically oxidised AMo2, BMo4, and CMo2 sample surfaces are shown in Fig.…”
Section: Chemical and Phase Analysis Of Selected Sample Surfacessupporting
confidence: 69%
“…Arsenic is naturally present in CaF 2 in the trivalent As-III state and is impossible to completely remove [39], which can explain why traces of As are present even in the purest commercially available hydrofluoric acid [40]. We observed a similar result for the surface of coarse-grained and nanostructured nitinol after etching the nitinol in hydrofluoric acid (HF 40%, for 1 min) [41]. The XRD patterns of the anodically oxidised AMo2, BMo4, and CMo2 sample surfaces are shown in Fig.…”
Section: Chemical and Phase Analysis Of Selected Sample Surfacessupporting
confidence: 69%
“…However, the alloy was more corrosion resistant in NaCl solutions. In other studies [91,95,96,97], no difference was found between the corrosion processes of micro- and nanostructured NiTi. However, nanostructured Ti was found to exhibit reduced corrosion resistance [98].…”
Section: Discussionmentioning
confidence: 81%
“…Investigations showed that in HCl nitinol in the nanosized state (grain diameter of 10 nm) reveals a significantly lower corrosion resistance than in the microstructural state because of an increase in the boundary length and in the amount of defects of the grain structure; and nitinol in NaCl, on the contrary, is more passive (consequently corrosion resistant) [26]. In the study [25,[27][28][29], there is no difference in corrosion processes between micro-and nanostructured nitinol. But in case of nanostructured titanium, corrosion resistance reduction was observed [30] though in all works positive influence on mechanical properties of materials was noted.…”
Section: Introductionmentioning
confidence: 96%